Is the handgrip strength performance better in judokas than in non-judokas? - Ache Dias, J.; Wentz, M.; Külkamp, W.; Mattos, D.; Goethel, M.; Borges Júnior, N. (Science & Sports, 2012)
Objectives: The aim of this study was to compare the handgrip strength performance between judokas and non-judokas. Equipment and methods: Twenty-two highly trained Brazilian judokas, all black belts, participating in the Brazil Trophy of Judo, and 18 non-judokas, both men, participated in the study. The handgrip strength was measured in both hands (dominant and non-dominant) during 10 s using a handgrip dynamometer and force-time parameters were obtained. The effects of judo practice and hand dominance on the force curve parameters were calculated. Results: No effects of judo practice and hand dominance on the peak grip force (P > 0.05), time to peak (P > 0.05) and impulse (P > 0.05) were found. The effect of judo practice on the fatigue rate (F = 4.253; P = 0.046; ?2 = 0.101) was found, but no effect of the dominance was detected. Conclusion: The results indicate that the judokas were not stronger than the non-judokas in absolute terms (peak grip force), but the judokas were more resistant to fatigue. This difference of fatigue resistance between judokas and non-judokas can be related to the characteristics of the judo practice, especially regarding the prolonged maintenance of the handgrip.